A Novel Single-Site Mutation in the Catalytic Domain of Protoporphyrinogen Oxidase IX (PPO) Confers Resistance to PPO-Inhibiting Herbicides - Rangani, Gulab; Salas-Perez, Reiofeli A.; Aponte, Raphael A.; Knapp, Michael; Craig, Ian R.; Mietzner, Thomas; Langaro, Ana Claudia; Noguera, Matheus M.; Porri, Aimone; Roma-Burgos, Nilda (Frontiers in Plant Science, 2019)
Protoporphyrinogen oxidase (PPO)-inhibiting herbicides are used to control weeds in a variety of crops. These herbicides inhibit heme and photosynthesis in plants. PPO-inhibiting herbicides are used to control Amaranthus palmeri (Palmer amaranth) especially those with resistance to glyphosate and acetolactate synthase (ALS) inhibiting herbicides. While investigating the basis of high fomesafen-resistance in A. palmeri, we identified a new amino acid substitution of glycine to alanine in the catalytic domain of PPO2 at position 399 (G399A) (numbered according to the protein sequence of A. palmeri). G399 is highly conserved in the PPO protein family across eukaryotic species. Through combined molecular, computational, and biochemical approaches, we established that PPO2 with G399A mutation has reduced affinity for several PPO-inhibiting herbicides, possibly due to steric hindrance induced by the mutation. This is the first report of a PPO2 amino acid substitution at this G399 position in a field-selected weed population of A. palmeri. The mutant A. palmeri PPO2 showed high-level in vitro resistance to different PPO inhibitors relative to the wild type. The G399A mutation is very likely to confer resistance to other weed species under selection imposed by the extensive agricultural use of PPO-inhibiting herbicides.